1995
DOI: 10.1902/jop.1995.66.11.1008
|View full text |Cite
|
Sign up to set email alerts
|

Familial Gingival Fibromatosis With Unusual Histologic Findings

Abstract: This article describes the occurrence of numerous calcifications, amyloid deposits, and islands of odontogenic epithelium in the gingiva of 3 siblings with familial gingival fibromatosis. These microscopic features have not been reported previously in patients with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 5 publications
2
38
0
1
Order By: Relevance
“…2,34, 35 We have not observed any calcified structures associated with odontogenic epithelial remnants in the gingiva. 36 An electron microscopic analysis of the ultrastructure of gingival connective tissue from one family of HGF patients who has been extensively studied 9,35 revealed collagen fibrils with structural abnormalities including diameter variations, as well as the presence of increased oxytalan and very few elastic fibers. 37 Previous reports examining the biological pathways that may influence HGF showed that the expression and production of MMP-1 and MMP-2 and their inhibitors, TIMP-1 and TIMP-2 were not altered, 16 while TGF-β production was two times higher in HGF fibroblasts compared to control fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…2,34, 35 We have not observed any calcified structures associated with odontogenic epithelial remnants in the gingiva. 36 An electron microscopic analysis of the ultrastructure of gingival connective tissue from one family of HGF patients who has been extensively studied 9,35 revealed collagen fibrils with structural abnormalities including diameter variations, as well as the presence of increased oxytalan and very few elastic fibers. 37 Previous reports examining the biological pathways that may influence HGF showed that the expression and production of MMP-1 and MMP-2 and their inhibitors, TIMP-1 and TIMP-2 were not altered, 16 while TGF-β production was two times higher in HGF fibroblasts compared to control fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…3 The most prominent pathologic manifestation of this disease is an excessive accumulation of extracellular matrix, predominantly type I collagen. 4,5 Many studies have shown increased transcriptional and translational levels of type I collagen in both tissue and fibroblast cultures derived from gingiva of HGF patients. [6][7][8] During the collagen biosynthesis, nascent single procollagen polypeptides, immediately after translation, undergo modification in the endoplasmatic reticulum, form triple helical chains, and are secreted as procollagen into the extracellular space via the Golgi apparatus.…”
mentioning
confidence: 99%
“…Stippled calcium may be present rather in juvenile aponeurotic fibroma. Calcified fibromatosis was also reported in gingiva and breast [14,15].…”
Section: Discussionmentioning
confidence: 87%